Peran Komunikasi Pemasaran Pengobatan Alternatif dalam Meningkatkan Kepercayaan Masyarakat - Angelia Putriana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This thesis contains research on the Role of Medicine Marketing Communication Alternative in Increasing Public Trust. This research aims to knowing the role of Accurate Health's alternative medicine marketing communication Center on the blog in increasing patient confidence. This research uses the method qualitative descriptive research, the data collection technique used is interview depth, literature, observation and documentation. Data analysis techniques using reduction, data presentation and drawing conclusions. To test the validity of this research using triangulation by comparing. The subject of this research is Fudin Pang, Akp, S.Psi, M.Psi and Accurate Health Center patients and the object is the role of Accurate Health Center marketing communications on the level of patient trust. The theory that use, communications, marketing communications, communication technology and trust. The results of this study indicate that the role of marketing communication in blogs has good role and very effective because of developing communication technology makes it easier for users to obtain information without looking at the user's status, everyone have also been able to manage existing new media (internet) communication technology and making each user more flexible. Through this research, it is also known that Each patient has their own level of trust and has their own way to convince themselves in their decision to take treatment.before deciding to do alternative medicine at Accurate Health Center.